Material Characterization and Optimum Usage of Coal Bottom Ash (CBA) as Sand Replacement against Concrete Properties - Ghadzali, Nor Syafiqah; Wan Ibrahim, Mohd Haziman; Mohd Zuki, Sharifah Salwa; Hisyam Sani, Mohd Syahrul; Mohammed Al-Fasih, Mohammed Yahya (International Journal of Integrated Engineering, 2020)
Generally known that the main constituent of concrete mixture is sand, coarse aggregates, cement and water. Presently, the deficiency of natural sand which is one of the raw materials turn into thoughtful issues in construction industry. To resolve the issue of natural sand depletion, industrial waste by-product should be utilized as an alternative material in concrete production. One of the industrial by-product that has an ability to be a replacement of sand in concrete is Coal bottom ash (CBA) which produced by coal based power plants. Therefore, this study aims to define the potentiality of CBA as sand replacement material in concrete. Initially, physical, chemical, microstructural properties like specific gravity, density, sieve analysis, X- ray fluorescence and scanning electron microscopic were investigated. Next, the optimum replacement of sand with CBA was determined based on the workability, compressive and splitting tensile test. The results showed that the CBA and sand have similarity in terms of physical properties. Whereas, according to chemical properties, CBA was classified as Class-F ash. It was found that 10% of CBA as sand replacement material gives the adequate strength and achieved the targeted/designed strength. It was concluded that CBA has good potential to be utilize as sand replacement material.